2017
DOI: 10.1364/oe.25.023773
|View full text |Cite
|
Sign up to set email alerts
|

Dual polarization split lenses

Abstract: We report the realization of polarization sensitive split lens configurations. While split lenses can be used to easily generate different types of controlled structured light patterns, their realization has been limited so far to scalar beams. Here we propose and experimentally demonstrate their generalization to vectorial split lenses, leading to light patterns with customized intensity and state of polarization. We demonstrate how these polarization split lenses can be experimentally implemented by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The two independent channels are used to produce two basis holographic vector components with an orthogonal polarization direction for their later combination. The phase-only LCOS SLMs are sensitive to the polarization state of the input light due to the operating principle of liquid crystal modules [32][33][34][35][36]. This means that the polarization state of input light needs to be parallel to the alignment direction of liquid crystal molecules for phase-only modulation.…”
Section: The Encoding Principle Of the Proposed Methodsmentioning
confidence: 99%
“…The two independent channels are used to produce two basis holographic vector components with an orthogonal polarization direction for their later combination. The phase-only LCOS SLMs are sensitive to the polarization state of the input light due to the operating principle of liquid crystal modules [32][33][34][35][36]. This means that the polarization state of input light needs to be parallel to the alignment direction of liquid crystal molecules for phase-only modulation.…”
Section: The Encoding Principle Of the Proposed Methodsmentioning
confidence: 99%
“…Some authors have shown the interest of generalizing the Billet-lens scheme to N -split lens sectors 29 , 32 , 33 . The coordinate system chosen to split the lens, strongly influences the light-dots distribution that can be created at the focal plane by using split schemes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…PA-LCoS can be found in many optics and photonics applications such as in diffractive optics [6], optical storage [7,8], optical metrology [9], reconfigurable interconnects [10,11], wavefront sensing of structured light beams [12], holographic optical traps [13], or quantum optical computing [14]. In recent years, a wide interest has arisen dealing with the generation and detection of unconventional polarization structured wavefronts [15,16] in which PA-LCoS devices play a central role [17,18].…”
Section: Introductionmentioning
confidence: 99%